Analisis Kualitas Layanan Konsumen Terhadap Keunggulan Bersaing Jasa Transportasi Darat Pada Pt. Kereta Api Indonesia (Persero) Kelas Argo - Musnaini Musnaini (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2011)
This research was intended to verify and analyze the influences of service quality of the customer Argo class train Indonesia. Analysis method is descriptive statistical and Multiple regression with SPSS software. The sampling Technique was purposive sampling; the instrument to collect the data was questionnaire with e-mail of 116 customer of Argo class train. This research result a simultaneous analysis 84.7% of tangible variable (X1), reliability (X2), responsiveness (X3), Assurance (X4) and Empathy (X5) were positive significant and positive influence of train competitive advantage of PT. Kereta Api Indonesia (Argo Class).